Research on the Performance Evaluation of Tire Mold Suppliers: A Case Study of Company H - Lu, Qingyang (Journal of Global Economy, Business and Finance, 2026)
Against the backdrop of the supplier selection for tire molds at Company H, this paper systematically analyzes the current situation and problems of its supplier evaluation and constructs a supplier evaluation index system encompassing five dimensions: quality, contract fulfillment, technology, cost, and service. Through on - site investigations and expert interviews, both objective and subjective data are obtained. The entropy weight method is used to objectively assign weights to each index, and the TOPSIS method is combined to comprehensively rank five strategic cooperation suppliers. The research results show that Supplier B has the best comprehensive performance, followed by Supplier D and Supplier A. This paper not only provides a decision - making basis for the optimization of suppliers at Company H but also offers an operable method framework for supplier performance evaluation in manufacturing enterprises.